Blended learning in English language teaching - Monga Armas, Ana Liseth (2023)
The post-pandemic is a relevant issue within educational changes. Teachers and students had to combine teaching and learning modalities. Blended learning was considered as a methodology that supports these educational processes. That is why the objective of the research was to describe teachers' perceptions of blended learning to teach English in the post-pandemic period. This research project used a descriptive qualitative method. The data was collected through an open interview. Main finding to two English teachers from the Isidro Ayora School. The main findings showed that there is no difference in teachers' experiences with blended learning according to the educational level of the student. Blended Learning in the pandemic, was a change that teachers faced when teaching. Blended Learning in the post-pancem, was a transition and combination of methodologies for the adaptation of resources and Blended Learning Strategies in English had strategies and activities supported by the use of technological resources to improve students' skills. In conclusion, blended learning in the post-pandemic period leads to the implementation of activities and strategies that support face-to-face through the use of technological tools.